Unequal giving: monetary gifts to children across countries and over time - Julie M. Zissimopoulos; James P. Smith (Institute for the Study of Labor (IZA), 2010)
Money parents give their adult children may be important for the financing of a child's education or a first home, relaxing binding credit constraints or responding to a transitory income shock. Financial transfers however, may extend economic disparities across generations if the wealthy transfer considerable resources to their children while middle class and poor households do not. In this paper, we first examine annual gifts of money from parents to adult children in the United States and ten European countries using the 2004 waves of the Health and Retirement Study (HRS) and Survey of Health, Ageing and Retirement in Europe (SHARE). Second, utilizing the long panel of the HRS, we study the long-run behavior of parental monetary giving to children across families and within a family. We found that in all countries, some parents gave money to children, many did not, the amount was low, about 500 Euros annually per child, and varied by parental socio-economic status and public social expenditures. In the short term, parents in the U.S. gave money to a child to compensate for low earnings or satisfy an immediate need such as schooling. Over sixteen years, parents gave an average of about 38,000 to all their children, five percent gave over 140,000 and gave persistently. With time, the amount of money children in the same family received became more equal and a child's level of education was one of the few remaining sources of differences in money given to children. Overall, the annual amount of money parents gave adult children in any country was not enough to affect the distribution of resources within or between families in the next generation although the timing of transfers for schooling or housing may have a significant impact on an individual child. Annual parental transfers for college age children in school in the U.S. were substantially higher than average transfers to all children. The effect of parental transfers for higher education on intergenerational mobility in the U.S. will depend in part upon whether this financing is essential in the schooling decision.
Keywords: J10; 330; Transfers; Privater Transfer; Eltern; Kinder; Soziale Ungleichheit; USA; EU-Staaten